IMMU-50. SYSTEMIC ADOPTIVE TRANSFER IMMUNOTHERAPY WITH TCR-TRANSDUCED T-CELLS TARGETING NY-ESO-1 FOR MENINGIOMA. (11th November 2019) - Sun, Matthew; Orpilla, Joey; Contreras, Erick; Treger, Janet; Molaie, Donna; Tsang, Jonathan; Antonios, Joseph; Wang, Anthony; Liau, Linda; Prins, Robert; Everson, Richard
Abstract: INTRODUCTION: The lack of immunotherapeutic antigen targets selectively expressed on meningiomas have historically hindered its immunotherapy development. However, recent literature showed that in meningiomas, NY-ESO-1 is the most frequently expressed Cancer-Testis(CT)-antigen, which is a group of proteins silent in somatic cells but reactivated in cancers. NY-ESO-1 also has higher expression in higher-grade meningiomas. Decitabine is known to upregulate CT-antigens and augment immunotherapy. To evaluate systemic adoptive transfer for meningiomas, we tested the efficacy of NY-ESO-1 T-cell-receptor(TCR)-transduced T-cells in vitro and in vivo, and the role of decitabine in meningioma immunotherapy. METHODS: NY-ESO-1 TCR-Transduced T-cells were generated by double-transfection with supernatants from PG-13 retroviral packaging cell line encoding HLA-A*0201–restricted NY-ESO-1(157 – 165) -specific TCR. In vitro cytolysis was measured using the xCelligence Real-Time Cell Analyzer System. We utilized human meningioma cells SF1335(Grade I, HLA-A2.1 positive) and CH157(Grade III, HLA-A2.1 negative) in vitro and in vivo. RESULTS: CH157 and SF1335 have high and low NY-ESO-1 expression, respectively. Decitabine upregulated NY-ESO-1 mRNA expression in SF1335 by 6-fold after 2 days and by 100-fold after 9 days, with similar effect on protein expression. Co-culturing CH157, CH157-HLA-A2.1(CH157 transduced with HLA-A2.1 vector), SF1335, and decitabine-pretreated-SF1335 cells individually with NY-ESO-1 TCR transduced T-cells at a ratio of 1:1 resulted in 0%, 65%, 20% and 40% cytolysis at 10hours, respectively. Systemic(intravenous) adoptive transfer of TCR-transduced T-cells significantly increased overall survival in NSG mice with intracranial xenografts of CH157-HLA-A2.1 (p=0.04) and SF1335(not treated with decitabine) (p=0.06). CONCLUSIONS: NY-ESO-1 TCR-transduced T-cells induce NY-ESO-1 and HLA-A2.1-specific cytolysis in meningioma in vitro, and systemic adoptive transfer confers a statistically significant survival benefit in vivo for meningiomas with high NY-ESO-1 expression. Decitabine upregulates NY-ESO-1 expression and increases tumor cytolysis by TCR-transduced T-cells in meningiomas. Targeting NY-ESO-1 may be a clinically feasible immunotherapeutic strategy to treat aggressive meningiomas.